Human remains and identification : Mass violence, genocide, and the 'forensic turn' - Gessat-Anstett, Élisabeth; Dreyfus, Jean-Marc (Book collections on Project MUSE., 2015)
A pioneering investigation into the practices and methodologies used in the search for and exhumation of dead bodies resulting from mass violence.